Analysis of Productive Zakat Distribution and Management Practices at LAZ (Amil Zakat Institution) Sidogiri, Pasuruan, East Java - sifak, mukhammad (Jurnal Ilmiah Ekonomi Islam, 2024)
The aim of this research is to describe the management of productive zakat at LAZ Sidogiri and to analyze how productive zakat distribution practices are carried out at LAZ Sidogiri. Design/methodology/approach The design of this research is qualitative. Qualitative research is research to describe and analyze phenomena, events, social activities, attitudes, beliefs, perceptions, thoughts individually and in groups with specific objectives. The result was that the implementation of Rasulullah's management at the Sidogiri Amil Zakat Institution (LAZ) was carried out according to the rules, generally after centralization. This is not surprising because the Sidogiri Islamic Boarding School (PPS) is an Islamic boarding school that has long been associated with the Islamic religion and contains the ideology of its founder, Muhammad SAW, who taught his followers about the correct interpretation and application of Islamic teachings as well as their own teachings. teachings . In this way, the use of management applications automatically does not deviate from the professional standards set by Allah Ta'ala. The management system described here is called SIFAT (Siddiq, Istiqomah, Fathanah, Amanah, and Tabligh).